Exploring the moderating role of context satisfaction between job characteristics and turnover intention of employees of Indian public sector banks. Issue 8 (10th August 2015) - Ghosh, Piyali; Rai, Alka; Chauhan, Ragini; Gupta, Nitika; Singh, Anamika
Abstract : Purpose: – An employee's satisfaction with the work context may affect her/his perception of the organization and may hence be a predictor of her/his intention to leave. The purpose of this paper is to explore the possible mediating role of context satisfaction between employees' perception of job characteristics and their turnover intention and rests on the Job Characteristics Model (JCM). Design/methodology/approach: – Hierarchical regression analysis was used to test the moderation hypothesis on sample data of 214 employees of 19 public sector banks in India. The population comprised both junior and middle management grade employees as these are expected to succeed retiring middle and senior management employees. Findings: – Findings suggest that in addition to enriched jobs, context satisfaction is critical to establish a positive environment to lessen turnover intention of employees. This highlights the need for a positive and supportive work context to maximize the benefits of jobs with positive characteristics. Originality/value: – The study is important for academicians and practitioners alike as it is evidence to the underlying process of how perception towards job characteristics together with work context as a less researched construct of JCM may influence intention to quit. The findings find relevance in the Indian banking sector, where retaining talent is a major challenge.